2018
DOI: 10.1016/j.jsat.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual versus group female-specific cognitive behavior therapy for alcohol use disorder

Abstract: Findings support the feasibility, acceptability, and efficacy of a group format for female-specific CBT for AUD, a new 12-session, single gender, community friendly, group therapy with programming specifically for women. Similar, positive outcomes for individual and group treatment formats were found for drinking, mood, coping skills, self-confidence, interpersonal functioning, and self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 59 publications
1
31
0
2
Order By: Relevance
“…The number of subjects involved in the intervention of Cognitive Behavior Therapy varied among the studies. For example, 55 people (Farren et al, 2015), 4 people (Besenius et al, 2013), 17 people (Arnedt et al, 2011), and 155 people (Epstein, 2018). Other varieties can be seen in other studies.…”
Section: Research Subjects and Comorbid Disordersmentioning
confidence: 56%
See 1 more Smart Citation
“…The number of subjects involved in the intervention of Cognitive Behavior Therapy varied among the studies. For example, 55 people (Farren et al, 2015), 4 people (Besenius et al, 2013), 17 people (Arnedt et al, 2011), and 155 people (Epstein, 2018). Other varieties can be seen in other studies.…”
Section: Research Subjects and Comorbid Disordersmentioning
confidence: 56%
“…For example, the experimental group was given treatment in the form of computer-based cognitive therapy for 5 hours, inpatient rehabilitation care for 4 weeks, and a follow-up for 3 months, while the control group did not get treatment like the experimental group (Farren et al, 2015 ). Besides, one group was given Female-Specific Cognitive Behavioral Therapy (G FS-CBT) while the other group was given individual Female-Specific Cognitive Behavioral Therapy (I-FS-CBT) (Epstein et al, 2018), or the group given Behavior Couple Therapy was compared to groups given Individual Cognitive Behavior Therapy (Vedel et al, 2008), and the group given Cognitive Behavior Therapy was compared to the group with Cognitive Behavior Therapy plus Supportive Counseling (Sannibale et al, 2013),…”
Section: Methodsmentioning
confidence: 99%
“…For the current secondary analyses, we drew data from women who were randomized to the individual FS-CBT condition ( n =35; other conditions were not female-specific). The second RCT (Study 2) randomized women to either individual FS-CBT or group FS-CBT (Epstein et al, under review). Data from 111 women in Study 2 were used for the current analyses (see below for details), for a total sample of 146 women in the current analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that women with AUD have a distinct clinical presentation and course of the disorder from men with AUD (Epstein & Menges, 2013), and gender differences exist in antecedents of relapse and mediators of treatment change (Epstein et al, under review). For instance, issues related to interpersonal functioning, emotion and mood regulation, and self-care have been shown to be particularly prevalent and relevant among women with AUD compared to men with AUD (Walitzer & Dearing, 2006; Timko, Finney, & Moos, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation